2001
DOI: 10.1016/s0006-3495(01)75716-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Hydration of the DNA-Human Topoisomerase I Covalent Complex

Abstract: The structure and hydration of reconstituted human topoisomerase I comprising the core and the carboxyl-terminal domains in covalent complex with 22-basepair DNA duplex has been investigated by molecular dynamics simulation. The structure and the intermolecular interactions were found to be well maintained over the simulation. The complex displays a high degree of flexibility of the contact area, confirmed by the presence of numerous water-mediated protein-DNA hydrogen bonds comparable in quantity and distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…Two MD simulation studies have indicated the occurrence of long range communications between different topoisomerase domains (33,34). A specific long range communication, involving the drug binding region, the geometry of the active site, and the linker domain has been demonstrated by the differential detection of the linker domain through x-ray diffraction only in the topoisomerase-DNA complex in the presence of Topotecan (8).…”
Section: Effect Of Cpt On the Cleavage-religation Equilibrium-tomentioning
confidence: 99%
“…Two MD simulation studies have indicated the occurrence of long range communications between different topoisomerase domains (33,34). A specific long range communication, involving the drug binding region, the geometry of the active site, and the linker domain has been demonstrated by the differential detection of the linker domain through x-ray diffraction only in the topoisomerase-DNA complex in the presence of Topotecan (8).…”
Section: Effect Of Cpt On the Cleavage-religation Equilibrium-tomentioning
confidence: 99%
“…The following modifications were made to this structure: (i) the iodouracils were converted to thymines; (ii) the crystallographic water molecules, except for the long-life [30] bridging water doubly hydrogen bonded to protonated Arg488 and ionized Asp533, were removed; (iii) hydrogen atoms were added to both the DNA and the enzyme; and (iv) the entire complex was energy minimized using the Tripos force field to the conjugate gradient of 1 kcal/(mol Å ).…”
Section: Construction Of the Ternary Complexesmentioning
confidence: 99%
“…Both these regions have been shown to form several direct and water-mediated contacts with the DNA phosphate groups in the strands downstream of the scissile base (5,11,13). It is worth noting, therefore, that the greater changes of dynamics and structure, in the absence of DNA but in the closed conformation, are located in the two regions involved in the controlling of the rotation of the scissile strand during the relaxation step.…”
Section: Resultsmentioning
confidence: 99%
“…Starting from the hTop1 closed crystallographic structure, the flexibility of the different domains have been monitored, but it has not been possible to monitor the so-called open state conformation, because of the strict non-covalent interactions occurring between the protein domains and DNA (11). MD can also be applied to sample large conformational changes after introducing a perturbation or a force that imposes the system to sample events occurring on a timescale not accessible by the current computational resources.…”
Section: Introductionmentioning
confidence: 99%